A highly antibacterial polymeric hybrid micelle with efficiently targeted anticancer siRNA delivery and anti-infection in vitro/in vivo. Issue 36 (10th September 2018) - Zhou, Li; Xi, Yuewei; Chen, Mi; Niu, Wen; Wang, Min; Ma, Peter X.; Lei, Bo
Abstract : Most of the diseases such as tumors are usually accompanied by microbial infection especially after surgical operation, which prevents successful cancer therapy. Abstract : Most of the diseases such as tumors are usually accompanied by microbial infection, especially after surgical operation, which prevents successful cancer therapy. It is necessary to develop a safe and efficient siRNA delivery vector with high anti-bacterial capability. Here, three multifunctional polymeric hybrid micelles (PHM1, PHM2 and PHM3) with high antimicrobial activity were prepared by mixing polymers PEG- b -P3/4HB- b -PEI- b -FA (EHP-FA) and PEG- b -P3/4HB- b -EPL (EHE) copolymer at different mixing ratios and evaluated for targeted siRNA delivery and anti-infection applications. The PHM micelles, taking advantage of the binding ability of EHE and the protection ability of EHP-FA, could effectively combine, protect siRNA, release complexed siRNA and target cancer cells. Additionally, PHM micelles displayed good hemocompatibility, lower cytotoxicity and higher gene silencing efficiency than commercial PEI (25 kDa) in A549, HeLa, HepG2 and C2C12 cells. Through optimizing the ratio of EHP-FA and EHE, PHM/sip65 showed a high p65 gene silencing efficiency above 90% in various cancer cells, which were significantly higher than EHP-FA/sip65 alone and EHE/sip65 complexes. Furthermore, PHM2 micelles showed excellent antimicrobial activity towards positive bacteria ( S. aureus ) in vitro and in vivo . Our study may provide a facile strategy to develop multifunctional polymer gene vectors for highly promising siRNA delivery and anti-infection.